Cigarette smoking and HIV: more evidence for action. - Reynolds, Nancy R (AIDS education and prevention : official publication of the International Society for AIDS Education, 2009)
As many as 50-70% of persons infected with HIV are current smokers. Compelling evidence concerning the risks of cigarette smoking to persons living with HIV urges the inclusion of smoking treatment protocols in contemporary models of HIV care. Yet in spite of growing awareness of this problem, persons living with HIV are not being effectively treated for tobacco use. To further an understanding of contributing factors and define directions for evidenced-based intervention, factors associated with smoking behavior among persons living with HIV are examined.
Keywords: Antiretroviral Therapy, Highly Active; Depression; Evidence-Based Practice; Female; HIV Infections; Homosexuality, Male; Humans; Male; Patient Compliance; Smoking; Smoking Cessation; Socioeconomic Factors